2006
DOI: 10.1211/jpp.58.6.0006
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 neutralizing antibodies elicited by the candidate CBD1 epitope vaccine react with the conserved caveolin-1 binding motif of viral glycoprotein gp41

Abstract: To date, candidate HIV-1 vaccines that have been tested in clinical trials have failed to induce broadly neutralizing activities and/or antibodies that inhibit infection by primary isolates of HIV-1. We recently identified a conserved caveolin-1 binding motif, WNNMTWMQW, in the ectodomain of HIV-1 transmembrane envelope glycoprotein gp41. We designed the synthetic CBD1 peptide SLEQIWNNMTWMQWDK, corresponding to the consensus caveolin-1 binding domain (CBD) in gp41, and showed that it elicits in rabbits the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…A recent study demonstrated that caveolin-1 interacts with HIV-1 envelope proteins (gp41) and potentially facilitates entry (Hovanessian et al, 2004). A number of reports have indicated that caveolin-1 plays some role in modulating viral pathogenesis in vivo (Benferhat et al, 2009a; Benferhat et al, 2009b; Benferhat et al, 2008; Fermin and Garry, 2005; Hovanessian et al, 2004; Huang et al, 2007; Rey-Cuille et al, 2006; Wang et al, 2010). Based on some of our previous studies on the role of cholesterol in HIV-1 biology, we initially suspected that the mechanism of HIV-1 inhibition by caveolin would be linked to its role as a cholesterol transporter.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that caveolin-1 interacts with HIV-1 envelope proteins (gp41) and potentially facilitates entry (Hovanessian et al, 2004). A number of reports have indicated that caveolin-1 plays some role in modulating viral pathogenesis in vivo (Benferhat et al, 2009a; Benferhat et al, 2009b; Benferhat et al, 2008; Fermin and Garry, 2005; Hovanessian et al, 2004; Huang et al, 2007; Rey-Cuille et al, 2006; Wang et al, 2010). Based on some of our previous studies on the role of cholesterol in HIV-1 biology, we initially suspected that the mechanism of HIV-1 inhibition by caveolin would be linked to its role as a cholesterol transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Ovalbumin (OVA, Sigma, St. Louis, MO) and HIV peptide (HIV-p) which is derived from the caveolin binding domain of the HIV-1 gp41 (aa 618−637: SLEVIWNNMTWMEWEREIDN) [13] were first used as the model antigens to test the adjuvanticity of the ASP-1 protein. The OVA was selected because it does not usually induce immune responses without the help of adjuvants [14,15].…”
Section: Model Antigensmentioning
confidence: 99%
“…As described previously [26][27][28][29][30], the truncated fragments of TFPR1 were designed and inserted into the pQE-30 vector (containing 6 × His-tag coding sequence), and expressed in E.coli. Because the recombinant proteins were expressed in the form of inclusion bodies, after the proteins were purified by Ni-NTA chromatography and dissolved in 8 M urea, the soluble denatured proteins were refolded by gradient dialysis in 6 M, 4 M and 2 M urea in tris-glycine buffer, followed by Laemmli buffer and PBS.…”
Section: Expression Purification and Structure Prediction Of Differmentioning
confidence: 99%
“…To verify whether purified TFPR1 has the capacity to enhance the immunogenicity of B cell epitope-based peptide antigen, HIV-1 CBD [28,29], a 20 aa HIV-1 gp41 peptide, was synthesized and used as immunogen. BALB/c mice were immunized intramuscularly with HIV-1 CBD in the presence or absence of TFPR1, and alum was used as an adjuvant control.…”
Section: Tfpr1 Acts As An Effective Adjuvant For Peptide Antigen Hiv-mentioning
confidence: 99%